Economic and Financial Drivers of Ocean Economy: Empirical Insights from European Economy - Zeeshan, Hafiz (My University, 2026)
This thesis takes a look at the key elements that contribute to the ocean economy in nations that are affiliated with the European Union. Particular attention is paid to taxation, coastal demographics, and commodity pricing, financial development, and inflation. This study makes use of empirical data derived via System Generalised Method of Moments (SGMM) estimations and robustness testing in order to determine the factors that have the most important influence on economic activity that is related with the ocean. Statistics show that the expansion of the coastal population and the increase in taxation both contribute positively to the economy of the ocean, despite the fact that inflation has a negative impact on maritime economies. On the other hand, there is no conclusive association between the economic performance of the ocean and the pricing of goods, the growth of the financial sector, or the exchange rates of currencies. On the basis of these data, one can get the conclusion that in order to boost the economic growth of the ocean, the government ought to give priority to the implementation of appropriate tax systems, the establishment of sustainable coastal districts, and the regulation of inflation. Through the provision of actual data on the economic factors that influence ocean-based businesses, the study contributes to the enhancement of the current body of knowledge. The purpose of this initiative was to exert an effect on the regulations that govern the construction of healthy maritime ecosystems inside the European Union.
Keywords: economic development; sustainable development; national economy; blue economy; economic growth; taxation; population; inflation (economics); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance